Impact of Workplace Factors on Role-Related Stressors and Job Stress Among Community Corrections Staff. (October 2019) - Rhineberger-Dunn, Gayle; Mack, Kristin Yagla
Community corrections staff are responsible for supervising more than 4 million offenders nationwide; yet, little research exists on understanding their experiences with role-related stressors and job stress. The purpose of this study was to extend the existing community corrections literature by examining the impact of job characteristics, danger-related factors, and role preference on role-related stressors (i.e., role conflict, role ambiguity, and role overload) and job stress, with a focus on determining whether the relationships varied across specific job positions (i.e., probation/parole vs. residential). Results indicated that each type of role-related stressor was differentially affected by job characteristics, danger-related factors, and role preference, and that these relationships also differed by position. Threat of harm was a significant predictor of each type of role-related stressor for probation/parole officers, but only had a significant effect on role overload for residential officers. Furthermore, safety training had significant effects on role ambiguity and role overload for residential officers, but was not a significant predictor of any role stressor for probation/parole officers. Role preference was significant for both positions, but only for the role overload variable. Most surprisingly, the only variable to predict job stress was role overload.